2017
DOI: 10.1002/adhm.201700701
|View full text |Cite
|
Sign up to set email alerts
|

Glycan Stimulation Enables Purification of Prostate Cancer Circulating Tumor Cells on PEDOT NanoVelcro Chips for RNA Biomarker Detection

Abstract: A glycan-stimulated and poly(3,4-ethylene-dioxythiophene)s (PEDOT)-based nanomaterial platform is fabricated to purify circulating tumor cells (CTCs) from blood samples of prostate cancer (PCa) patients. This new platform, phenylboronic acid (PBA)-grafted PEDOT NanoVelcro, combines the 3D PEDOT nanosubstrate, which greatly enhances CTC capturing efficiency, with a poly(EDOT-PBA-co-EDOT-EG3) interfacial layer, which not only provides high specificity for CTC capture upon antibody conjugation but also enables co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 74 publications
(45 reference statements)
0
44
0
1
Order By: Relevance
“…Several techniques are available for the recovery of cells intact from microfluidic devices [4345, 49, 50]. Here, we employed an air foam approach—using a mixture of air and cell culture medium containing bovine serum albumin (BSA)—for the efficient release of the captured cancer cells from our microfluidic devices (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several techniques are available for the recovery of cells intact from microfluidic devices [4345, 49, 50]. Here, we employed an air foam approach—using a mixture of air and cell culture medium containing bovine serum albumin (BSA)—for the efficient release of the captured cancer cells from our microfluidic devices (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Glutathione (GSH) and excess thiol molecules were utilized to competitively exchange original thiol ligands, resulting in CTC release with over 90% efficiency and 78% cell viability ( Figure 6 D). Shen et al reported a phenylboronic acid (PBA)-grafted PEDOT NanoVelcro chip with anti-EpCAM antibody conjugated onto the nanosubstrate of the chip via PBA–oligosaccharide binding [ 107 ]. The introduction of glycan with stronger affinity to PBA results in competitive binding, allowing effective CTC release.…”
Section: Nanotechnology-assisted Circulating Tumor Cell (Ctc) Isolmentioning
confidence: 99%
“…Forming more stable chemical bonds by introducing ligand with stronger affinities is an alternative strategy of ligand‐competition release. Thereinto, boronic acid modified interfaces have attracted much interest for cell capture‐and‐release, since the formed cyclic esters between boronic acid with 1,2‐ or 1,3‐diols of oligosaccharide could be replaced by glycan . For example, Yu and co‐workers reported a glycan‐stimulated and phenylboronic acid (PBA)‐grafted nanosubstrate platform to purify prostate cancer CTCs .…”
Section: Ctc Releasementioning
confidence: 99%